Wczesnośredniowieczne grodzisko wklęsłe w Bninie koło Poznania w świetle dotychczasowych ustaleń dendrochronologicznych - Kara, Michał; Przybył, Maciej (Folia Praehistorica Posnaniensia, 2018)
The article presents results of dendrochronological investigations of wooden constructions of the rampart of early medieval stronghold in Bnin (current location Kómik-Bnin), of which a well preserved stone-wooden-earthen fortifications are among the best recognized in Wielkopolska. The site was excavated in the years 1961-1969. The relicts of two phases of the rampart construction discovered in so-called northern trench were dated to the end of the 12,h - beginning of the 13lh century. Based on results of dendrochronological dates of 25 samples taken in 1994, a discovered part of the rampart was constructed in two phases with a break in the year 939. The older construction was finished in 938, while the younger one in 940.